Inflammation and Lung Cancer - Dubinett, Steven M. (Springer New York : Imprint: Springer, 2015)
This volume  presents aspects of the inflammatory tumor microenvironment (TME) and its many roles in tumor progression and metastasis, including creation of a hypoxic environment, increased angiogenesis and invasion, changes in expression of microRNAs (miRNAs), and an increase in a stem cell phenotype. The volume also covers the mechanisms of inflammatory mediators. Chronic overexpression of inflammatory mediators in the TME, as seen in smokers and patients with non-small cell lung cancer (NSCLC), can also lead to increased tumor initiation, progression, invasion, and metastasis. The volume will provide a comprehensive perspective of the latest findings and summaries of progress made regarding inflammation and its connection to lung cancer.